Editing and juxtaposition in Kim Kardashian’s Instagram stories - Lepri, Adil Giovanni (AoIR Selected Papers of Internet Research, 2026)
The article analyzes Kim Kardashian's Instagram Stories through the lens of film studies, viewing 24h worth of posts as single video streams. With an approach grounded in film analysis inspired by the poetics of film (Bordwell, 1989) and Eisenstein’s (1988) theory of montage, the study examines the effects of editing and juxtaposition of stories in shaping an user’s online presence. Preliminary findings reveal a visual tension between static and moving images, highlighting the rhythmic and visual shock caused by abrupt cuts between story segments. The study also observes the fusion of multimodality and cross-platform interactions, such as images of magazine articles and political support posts, creating a combination of seemingly disconnected content that, when viewed in sequence, produces an artistic and shocking effect. Despite limitations, such as the arbitrary choice of profile and the restricted corpus, the study concludes that Instagram Stories can be seen as artistic works, albeit unintentional, constructed through an editing process that involves the user and the platform in a hybrid human-technical process. Kardashian's stories, multifaceted and contradictory, offer a view of the construction of her online persona, highlighting activist content in an unexpected but effective way.